Environmental Pollution and its Impact on Human Health: Advances in Medicinal Chemistry for Detoxification and Disease Prevention - Saeed, Hadeel Haider; shker, Shimaa adnan; Hadi, Eman Shaker (American Journal of Biodiversity, 2025)
Environmental pollution remains a critical global issue that directly affects human health through complex exposure pathways involving air, water, soil, and food contamination. Despite growing awareness, there is a considerable knowledge gap in understanding the cumulative and synergistic health effects of emerging pollutants, including trace metals, endocrine disruptors, and airborne particulates. This paper presents an integrative review of environmental toxicology, highlighting epidemiological evidence, pollutant classification, and mechanisms of action, alongside recent advancements in medicinal chemistry for detoxification. The method involves a multidisciplinary literature synthesis across environmental sciences, toxicology, and pharmaceutical innovations, with a focus on phytochemicals, antioxidants, and bioremediation strategies. The implications underscore the urgent need for holistic health frameworks, combining environmental monitoring, public health policy, and therapeutic innovation to mitigate pollution-induced diseases and support preventive health systems.